Pengaruh Pola Pikir, Kreativitas, Dan Motivasi Berwirausaha Terhadap Minat Berwirausaha (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Sholeh, Abdurrahman; Askandar, Noor Shodiq; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research endeavors to comprehensively explore how variations in mindset, the expression of creativity, and the presence of entrepreneurial motivation collectively and individually relate to the inclination toward entrepreneurial engagement among students of the Islamic University of Malang. The focal population of the investigation consists exclusively of individuals who have previously undertaken formal coursework in Entrepreneurship. From this group, a total of 75 participants were systematically selected through the application of the Maholtra sampling formula to ensure methodological precision. Within the constructed research framework, entrepreneurial interest is designated as the dependent construct, whereas mindset, creativity, and entrepreneurial motivation are positioned as the independent constructs under scrutiny. Through analytical procedures, the findings affirm that each independent variable—mindset, creativity, and entrepreneurial motivation—exerts a distinct and partial influence upon the degree of entrepreneurial interest demonstrated by the students involved. Keywords: Entrepreneurial Interest, Mindset, Creativity, And Entrepreneurial Motivation